Anti-Inflammation and Anti-Fibrotic Effects of Amniotic Membrane on Post-Trabeculectomy Conjunctiva (Experimental Research on Oryctolagus cuniculus) - Listya Dyah Rihardini; Suparman Suparman; Evelyn Komaratih (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To evaluate the effects of amniotic membrane transplantation on the modulation ofwound healing after trabeculectomy.Methods: Eighteen eyes of nine New Zealand rabbits: nine left eyes underwent glaucoma filteringsurgery, nine right eyes underwent trabeculectomy and amniotic membrane transplantation. Freshfrozen human amniotic membranes were transplanted above scleral flap, below the conjunctiva withthe stromal side-up. Daily examination of anterior segment were performed using hand held slit lamp.After 7 days, all eyes were enucleated and sent for histopathology examination to evaluate theinflammatory and fibroblast cells. The rabbits were terminated. Blebs were well formed until 7 days.Results: There were statistically no significant difference between two groups in quantity ofinflammatory cells (p=0.258) and fibroblast cells (p=0.436). The tendency in the treatment group,however, the Masson’s Trichrome obtained less fibrosis (88.9%) compared to the control group(44.4%). Hematoxilin eosin staining revealed inflammatory reaction tends to be more severe than thecontrol group, suggesting a xenograft rejection.Conclusion: AMT is still potential as an alternative option to reduce fibrosis in glaucoma filteringblebs but need further research. In rabbits, human amniotic membrane elicited a xenograft reaction.Keywords: amniotic membrane, trabeculectomy, inflammation, fibrosis